2022
DOI: 10.1589/jpts.34.218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a controlled starting position on the relationship between the forward reach distance and movement distance of the center of pressure in the functional reach test using the ankle joint strategy

Abstract: [Purpose] This study aimed to clarify whether the distribution range of the forward reach distance and the relationship between the forward reach distance and the movement distance of the center of pressure differed depending on whether the controlled starting standing position during the functional reach test with an ankle joint strategy. [Participants and Methods] Sixteen healthy male volunteers participated in the study. The distribution range of the forward reach distance and the relationship between the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In Measurement 2, the FRT was performed under two conditions: CSP and non-CSP. Reflex markers were affixed to the participants’ right acromial process (one marker in the resting standing position and another one at 90° flection of the upper limbs), great trochanter, processus styloideus ulnae, and third metacarpal head before the anterior reach measurement 17 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Measurement 2, the FRT was performed under two conditions: CSP and non-CSP. Reflex markers were affixed to the participants’ right acromial process (one marker in the resting standing position and another one at 90° flection of the upper limbs), great trochanter, processus styloideus ulnae, and third metacarpal head before the anterior reach measurement 17 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Consequently, results have been inconsistent regarding the relationship between reach distance and SBA in older adults. One reason for the lack of consistent results may be that the start position in the FRT is typically not well controlled 15 , 16 , 17 ) . Duncan et al 18 ) reported that only the foot position was controlled as the start position in the FRT.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations